Chalcone Derivatives: Synthesis and Cytotoxicity Assays - Ahmed, Ahmed; H. Ahmed, Asraa; Jelassi, Haikel (Al-Nahrain Journal of Science, 2024)
The research included the formation of chalcone derivatives, which are organic materials with biological importance, on which this research is based. The Chalcone derivatives were synthesised from the Claisen-Schmidt condensation reaction. Compounds I-III were synthesised by reacting p-aminoacetophenone with (4-methylbenzaldehyde, 2,3-dimethylbenzaldehyde, and cinnamaldehyde), respectively, in an ethanolic solution of KOH (30%). Chalcones were characterised by Fourier transform infrared spectroscopy (FT-IR) and proton nuclear magnetic resonance (1H NMR). The cytotoxicity effect was demonstrated in human melanoma cells A-375 and HdFn normal cells, and the MTT results showed that the cytotoxicity of Chalcone derivatives was greater than HdFn cells. The ability to use Chalcone derivatives as sunscreen showed a promising result.